Doxorubicin-induced nephrotoxicity: the protective role of a standardized ethanolic extract of Andrographis paniculata leaves - Arozal, Wawaimuli; Eziefule, Oluebube Magnificient; Wanandi, Septelia Inawati; Louisa, Melva; Dewi, Syarifah; Nafrialdi,; Siregar, Nurjati Chairani; Makambwa, Ezekiel (Frontiers in Pharmacology, 2025)
IntroductionMulti-organ toxicity, including nephrotoxicity, is a major drawback to the use of doxorubicin in chemotherapy. This study investigated the protective effect and possible mechanism of action of a standardized ethanolic extract of Andrographis paniculata (Burm.f.) Wall. ex Nees leaves (EEAP) capsule formula against doxorubicin (DOX)-induced nephrotoxicity.MethodDOX was administered intraperitoneally, while the EEAP capsule formula was given orally at doses of 125, 250, and 500 mg/kg BW. Kidney tissues were analyzed for concentrations of nuclear factor kappa B (NF-κB), superoxide dismutase (SOD), and total antioxidant capacity (TAC); mRNA expression levels of inflammatory markers, including nucleotide-binding oligomerization domain, leucine-rich repeat, and pyrin domain-containing protein 3 (NLRP3) and interleukin-1 beta (IL-1ß), were measured; plasma levels of kidney function parameters such as urea, creatinine, and electrolytes (sodium and calcium) were quantified. Histopathological changes were assessed using hematoxylin and eosin staining. Additionally, molecular docking was conducted to evaluate the interaction between andrographolide and the target proteins affected by DOX.ResultAn increase in TAC concentration (p < 0.05), a decrease in NLRP3 mRNA expression (p < 0.05), and a reduction in serum sodium concentration (p < 0.05) were observed following EEAP administration. Minimal pathological alterations were noted in the cotreatment groups compared to the DOX-only group. Molecular docking revealed that andrographolide showed favorable binding energies with the target proteins (approximately -5 to -8 kcal/mol).ConclusionIt is suggested that EEAP conferred renal protection against DOX-induced damage primarily through the attenuation of oxidative stress and inflammation, with andrographolide playing a significant role in the observed protective effects.